Uterine Prolapse: From Antiquity to Today - Keith T. Downing (Obstetrics and Gynecology International)
Uterine prolapse is a condition that has likely affected women for all of time as it is documented in the oldest medical literature. By looking at the watershed moments in its recorded history we are able to appreciate the evolution of urogynecology and to gain perspective on the challenges faced by today's female pelvic medicine and reconstructive surgeons in their attempts to treat uterine and vaginal vault prolapse.